Functional Pangenome Analysis Shows Key Features of E Protein Are Preserved in SARS and SARS-CoV-2 - Alam, Intikhab; Kamau, Allan A.; Kulmanov, Maxat; Jaremko, Łukasz; Arold, Stefan T.; Pain, Arnab; Gojobori, Takashi; Duarte, Carlos M. (Frontiers in Cellular and Infection Microbiology, 2020)
The spread of the novel coronavirus (SARS-CoV-2) has triggered a global emergency, that demands urgent solutions for detection and therapy to prevent escalating health, social and economic impacts. The spike protein (S) of this virus enables binding to the human receptor ACE2, and hence presents a prime target for vaccines preventing viral entry into host cells. The S proteins from SARS and SARS-CoV-2 are similar, but structural differences in the receptor binding domain (RBD) preclude the use of SARS-specific neutralizing antibodies to inhibit SARS-CoV-2. Here we used comparative pangenomic analysis of all sequenced reference Betacoronaviruses, complemented with functional and structural analyses. This analysis reveals that, among all core gene clusters present in these viruses, the envelope protein E shows a variant cluster shared by SARS and SARS-Cov2 with two completely-conserved key functional features, namely an ion-channel and a PDZ-binding motif (PBM). These features play a key role in the activation of the inflammasome causing the acute respiratory distress syndrome, the leading cause of death in SARS and SARS-CoV-2 infections. Together with functional pangenomic analysis, mutation tracking and previous evidence, on E protein as a determinant of pathogenicity in SARS, we suggest E protein as a therapeutic target for further studies to reduce complications of SARS-CoV-2 infections in COVID-19.